Русская история в жизнеописаниях ее главнейших деятелей - Костомаров Николай Иванович (1991)
Экземпляры: аб. (1992) / Инвентарный номер: 35166 / Цена: / Сис.шифр: 63.3(2)4 / Авт.знак: К 72 / ГРНТИ: 03.23.31 / ББК: 63.3(2)45